2017
DOI: 10.1186/s12882-017-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk scores to predict decreased glomerular filtration rate at 10 years in an Asian general population

Abstract: BackgroundAsians have among the highest prevalence of chronic kidney disease (CKD) or end-stage renal disease in the world. A risk score capable of identifying high risk individuals at the primary care level could allow targeted therapy to prevent future development of CKD. Risk scores for new CKD have been developed in US general populations, but the impact of various risks factors for development of CKD may differ in Asian subjects. In this study, we aimed to develop risk models and simplified risk scores to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…The kidney hemodynamics can be altered by these impacts, thereby affecting the progression of kidney diseases. 38 In this study, the gender was shown to be a predictive factor for the decreased GFR in Chinese general population, supported by the results of Saranburut et al 21 It is well known that GFR declines with age, which may be associated with the kidney structural changes. 39 At the macrostructural level, the volume of renal cortex reduces, surface coarseness augments, and the size and number of simple renal cysts raise with age; at the microstructural level, the histological characteristics of nephrosclerosis, such as tubular atrophy, interstitial fibrosis and glomerulosclerosis, are gradually evident with age.…”
Section: Ta B L E 3 Association Between Different Scores and The Decrsupporting
confidence: 82%
See 1 more Smart Citation
“…The kidney hemodynamics can be altered by these impacts, thereby affecting the progression of kidney diseases. 38 In this study, the gender was shown to be a predictive factor for the decreased GFR in Chinese general population, supported by the results of Saranburut et al 21 It is well known that GFR declines with age, which may be associated with the kidney structural changes. 39 At the macrostructural level, the volume of renal cortex reduces, surface coarseness augments, and the size and number of simple renal cysts raise with age; at the microstructural level, the histological characteristics of nephrosclerosis, such as tubular atrophy, interstitial fibrosis and glomerulosclerosis, are gradually evident with age.…”
Section: Ta B L E 3 Association Between Different Scores and The Decrsupporting
confidence: 82%
“…46,47 This risk scoring system may exert a better predictive effect on the decreased GFR if the Asian coefficient for CKD-EPI equation is adopted in eGFR. 21 Moreover, the eGFR was measured only once, which may result in an overestimation of incident CKD. It is thus necessary to conduct more studies with repeated Scr measurements to confirm whether the decreased GFR occurs.…”
Section: Ta B L E 3 Association Between Different Scores and The Decrmentioning
confidence: 99%
“…Therefore, there may be selection bias. Additionally, compared with previous studies [24][25][26], this study is relatively small. Second, external validation has not been carried out because there are no data available from other similar studies in China.…”
Section: Strengths and Limitationsmentioning
confidence: 83%
“…In a recent study conducted in low-to middle-income [26], age, sex, SBP, diabetes, and WC were significant predictors for their clinical score, while age, sex, SBP, diabetes, and eGFR were predictors in the combined clinical and laboratory model. Both risk scores had a high degree of accuracy and discriminatory power in the Thai population (AUC 0.72-0.79).…”
Section: Comparison With Other Risk Scoresmentioning
confidence: 89%
“…Diabetes, a chronic systemic metabolic disease characterized by long-term hyperglycemia, leads to glomerular filtration rate (GFR) decline via continuous impairment of renal function and has been the main cause in end stage renal disease (ERSD) [8]. The GFR decline still hasn't been inhibited though the treatment has been actively used in controlling risk factors such as blood sugar, blood pressure, blood lipid and the renin-angiotensin system [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%